2015
DOI: 10.1113/jphysiol.2014.286633
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activation of CB2 cannabinoid receptors in the hippocampus increases excitatory synaptic transmission

Abstract: Key pointsr The effects of cannabinoids are primarily mediated by two types of cannabinoid receptors, CB1 receptors in the nervous system and CB2 receptors in the immune system. r Recent evidence indicates that CB2 receptors are also widely expressed in the brain and involved in neuropsychiatric functions, such as schizophrenia-like behaviours, anxiety, memory, vomiting and pain. r The cellular mechanisms by which CB2 receptors regulate neuronal functions are unknown. r We show that chronic activation of CB2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 72 publications
5
90
0
Order By: Relevance
“…Interestingly, it has been shown that only chronic activation of CB2 increases excitatory synaptic transmission, whereas its short-term activation has little effect on synaptic activity (32). A therapeutic use of CB2 as antiobesity target might presume a related chronic neuronal activation, that, in turn, increasing excitatory synaptic transmission, should facilitate the peripheral antiobesity effects without exerting remarkable psychotropic activity.…”
Section: And Inhibiting Activated Macrophages and T-cells 22mentioning
confidence: 98%
“…Interestingly, it has been shown that only chronic activation of CB2 increases excitatory synaptic transmission, whereas its short-term activation has little effect on synaptic activity (32). A therapeutic use of CB2 as antiobesity target might presume a related chronic neuronal activation, that, in turn, increasing excitatory synaptic transmission, should facilitate the peripheral antiobesity effects without exerting remarkable psychotropic activity.…”
Section: And Inhibiting Activated Macrophages and T-cells 22mentioning
confidence: 98%
“…In both regions, CB 2 receptors appear to be mostly neuronal, influencing excitatory synaptic transmission, plasticity, and long-term potentiation (80–82). Subcellular fractionation techniques, western blotting, binding assays and electrophysiology data from prefrontal cortex slices show that CB 2 receptors are located intracellularly and that 2-arachidonoylglycerol (2-AG) activation results in inositol triphosphate 3 (IP 3 ) receptor-dependent opening of Ca 2+ -activated chloride channels and decreased neuronal excitability (74, 83, 84).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic activation of CB2Rs increases excitatory synaptic transmission (Kim and Li, 2015), whereas acute activation of CB2Rs reduces inhibitory synaptic transmission (Morgan et al, 2009) and neuronal excitability (Patel et al, 2003; Sagar et al, 2005; den Boon et al, 2012; Zhang et al, 2014a). However, the cellular mechanisms of CB2R functions are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For investigation of the mechanisms, it is important to determine the cellular location of CB2Rs in the brain because it may suggest the signaling pathways of CB2Rs. For example, if hippocampal CB2Rs are expressed only in interneurons as suggested (Lanciego et al, 2011), the effects of CB2Rs on pyramidal cells (Kim and Li, 2015) might occur via intercellular signaling mechanisms, but this critical matter is yet to be identified.…”
Section: Introductionmentioning
confidence: 99%